Antribacter gilvus gen. nov., sp. nov., a new member of the family Promicromonosporaceae from a karstic cavern. Issue 12 (18th September 2019) - Zhang, Ling-Yu; Fang, Bao-Zhu; Jiao, Jian-Yu; Zhang, Xiao-Tong; Liu, Lan; Meng, Xiao-Lin; Ming, Hong; Nie, Guo-Xing; Li, Wen-Jun
Abstract : A novel actinobacterium, designated strain CFH 30434 T, was isolated from a soil sample collected from a karst cave in Luoyang, Henan Province, PR China. The taxonomic position of the strain was investigated by using a polyphasic approach. Cells of the strain were aerobic, Gram-stain-positive, non-motile and coccoid or short rods. The strain was found to be oxidase-positive and weakly catalase-positive. Strain CFH 30434 T grew optimally at 28 °C, pH 7.0–9.0 and in the presence of up to 0–1.5 % NaCl (w/v). The whole-cell sugars were glucose, mannose and rhamnose. The major isoprenoid quinone was MK-9(H8 ) and the major fatty acids (>10 % of the total fatty acids compositions) were anteiso-C15 : 0, iso-C15:0 and iso-C14 : 0 . The polar lipids detected were diphosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside, an unidentified phosphoglycolipid, an unidentified phospholipid and an unidentified glycolipid. The genomic DNA G+C content was determined to be 72.3 mol%. The results of phylogenetic analysis of 16S rRNA gene sequences indicated that CFH 30434 T clustered within the family Promicromonosporaceae, and closely with the type strains of Xylanimicrobium pachnodae DSM 12657 T, Myceligenerans crystallogenes DSM 17134 T and Promicromonospora xylanilytica CCTCC AA 208046 T (97.3 %, 96.2 and 95.9 % sequence similarities, respectively). Phylogenetic analysis showed that strain CFH 30434 T formed a separate evolutionary branch, and was parallel to other related genera of Promicromonosporaceae . Its phylogenetic distinctiveness and distinguishing phenotypic characteristics supported that strain CFH 30434 T represents a novel genus of the family Promicromonosporaceae, for which the name Antribacter gilvus gen. nov., sp. nov. is proposed. The type strain is CFH 30434 T (=CGMCC 1.13856 T =KCTC 49093 T ).